How important are entrepreneurial passion, government support, and financial resource availability in improving SME performance? - Liana Mangifera; Muzakar Isa; Ali Zainal Abidin (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
This research examines entrepreneurial passion (EP) along with the possible outcomes on business performance among MSMEs. Entrepreneurial passion is an important factor that drives business success through the emotional strength that urges individuals to do whatever it takes to achieve their business goals, especially the food and manufacturing MSMEs in Surakarta. The objective of this research is precisely to identify entrepreneurial passion and its impact on business performance through the role of government support (GS) and financial resource availability (FRA). Based on the entrepreneurial identity approach of 180 MSMEs in the small manufacturing and food business sectors in the Surakarta Region, passion as a founder, inventor, or business developer on the impact of their business performance results was identified. The results revealed that EP and GS significantly affected MSME performance. The FRA did not significantly affect the MSME performance. In this case, GS partially mediates the influence of EP on performance, while FRA could not mediate the influence of EP on performance. This research implies that government support has an essential role in fostering an entrepreneurial passion in the context of small businesses that are still in the growth stage. In addition, MSME players need to know their character according to their passions to produce superior performance; this aligns with the personality-job fit theory